Dynamic distortion control for 3-D embedded wavelet video over multiuser OFDM networks - Su, Guan-Ming; Han, Zhu; Wu, Min; Liu, K.J. Ray (2004 IEEE Global Telecommunications Conference - Globecom, 2004)
In this paper, we propose a system to transmit multiple 3D embedded wavelet video programs over downlink multiuser OFDM. We consider the fairness among users and formulate the problem as minimizing the users' maximal distortion subject to power, rate, and subcarrier constraints. By exploring frequency, time, and multiuser diversity in OFDM and flexibility of the 3D embedded wavelet video codec, the proposed algorithm can achieve fair video qualities among all users. Compared to a scheme similar to the current multiuser OFDM standard (IEEE 802.11a), the proposed scheme outperforms it by 1-5 dB on the worst received PSNR among all users and has much smaller PSNR deviation.